Pengembangan Media Booklet Kimia Berbasis Inkuiri Terbimbing Pada Siswa SMA/MA - Hasdina Hasdina; Kuntum Khaira (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Using media in learning plays an important role in student understanding. Students will be more motivated to learn, speak and visualize. This makes the teaching and learning process more effective and efficient. Therefore, good learning requires teachers who are competent in managing, utilizing, and developing learning media. Various actions have been taken to ensure that learning media has a positive impact on students. The teacher acts as an intermediary to guide and guide students' learning. Teachers must be able to select and develop media while learning. Therefore, the development of visual learning media (i.e., booklet media) is needed. Beautifully designed booklet media, whose content is dominated by illustrations and images, enhances students' interest in learning and increases student activity. In order to get the most out of this booklet, it is necessary to adopt a methodology or learning model. The learning model is a guided inquiry model. In this study, using the R&D approach, the final phase comes in the form of a validation and practical phase. The results showed that the validity result of the Guided Inquiry-based chemistry brochure reached 90.87%, meeting the criteria of being very effective. From this, it can be concluded that the Guided Inquiry-based Chemistry Booklet as drafted is valid. From the practical results, that is, 78.25% of the students answered the questionnaires and met the practice standards. It can be concluded that the developed guided inquiry-based Chemistry Booklet is very useful.